Postnatal depression across cultures: a qualitative study in Malaysia - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (2015)
Background: Postnatal depression (PND) is one of the most common maternal mental health problems for women worldwide. Yet the wide range of reported rates of PND in different countries raises questions about how PND is experienced by women in different cultures and whether interventions developed in western cultures are appropriate in very different settings. It is important to establish how PND is defined, experienced and managed in different cultures in order to create culturally relevant interventions. yet there was no research have been published up to this date. No previous studies of women’s experience of PND and its management have been conducted in Malaysia.